MICAL-L1-related and unrelated mechanisms underlying elongated tubular endosomal network (ETEN) in human dendritic cells - Compeer, E; Boes, M (Taylor and Francis, 2014)
The endosomal pathway constitutes a highly dynamic intracellular transport system, which is composed of vesicular and tubular compartments. Endosomal tubules enable geometry-based discrimination between membrane and luminal content. Extended tubular endosomes were suggested to deliver a steady stream of membrane proteins to one location more reliable and effective than vesicular endosomes. Recently, we demonstrated that human dendritic cells (DCs) form a large elongated tubular endosomal network, e.g. ETEN, upon distinct triggers. LPS-stimulation triggered late endosomal tubulation. Additional clustering of class I MHC and ICAM-1 by a cognate interaction between antigen-laden DC and antigen-specific CD8+ T-cells induces formation of transferrin-positive tubules emanating from the endosomal recycling compartment (ERC). We here discuss cell-biological mechanisms that are involved in membrane bending and possibly underlie initiation, elongation, and stabilization of ETEN in human DCs. Using a knock-down approach we demonstrate that MICAL-L1 is necessary for ETEN remodeling originating from ERC in human DCs.